Decentralization in Kerala: Panchayat Government Discretion and Accountability - Venugopal, V. (2012)
Kerala is regarded as one of the most decentralized states in India. Through a 'big bang' approach, Kerala implemented a significant fiscal decentralization program and then built the capacity of its local governments. We employ a diagnostic framework to analyze its local government discretion and accountability in political, administrative and fiscal domains. We find that Kerala's local governments have a very high degree of discretionary power accompanied by a high degree of accountability towards citizens. But the areas of administrative accountability and financial management need to be strengthened. Also there may have been excessive focus and investment on social accountability mechanisms at the cost of local government discretion and formal public sector accountability mechanisms. Copyright (C) 2009 John Wiley & Sons, Ltd.